Politicization of migration in the countermedia style: A computational and qualitative analysis of populist discourse. (December 2019) - Ylä-Anttila, Tuukka; Bauvois, Gwenaëlle; Pyrhönen, Niko
Highlights: Countermedia are partisan media that oppose conventional media and the establishment. The Finnish right-wing populist countermedia, WTF, has a distinct discursive style. This style emphasizes crisis and threat resulting from immigration. In the Finnish Parliament, a similar style is used most by Finns Party politicians.